Banking in Africa - Beck, Thorsten; Cull, Robert (World Bank, Washington, DC, 2014)
This paper takes stock of the current state of banking systems across Sub-Saharan Africa and discusses recent developments including innovations that might help Africa leapfrog more traditional banking models. Using an array of different data, the paper documents that African banking systems are shallow but stable. African banks are well capitalized and over-liquid, but lend less to the private sector than banks in non-African developing countries. African enterprises and households are less likely to use financial services than their peers in other developing countries. The paper also describes a number of financial innovations across the continent that can help overcome different barriers to financial inclusion and have helped to expand the bankable and the banked population.